Triggers in Allodynic and Non‐Allodynic Migraineurs. A Clinic Setting Study. Issue 1 (26th December 2012) - Baldacci, Filippo; Vedovello, Marcella; Ulivi, Martina; Vergallo, Andrea; Poletti, Michele; Borelli, Paolo; Cipriani, Gabriele; Nuti, Angelo; Bonuccelli, Ubaldo
<x xml:space="preserve">Abstract</x> Background Allodynia is considered a phenomenon of central sensitization that may lead to migraine transformation, lowering the attack threshold. Migraine triggers are factors that may induce headache attacks in susceptible individuals. We hypothesize that because allodynia decreases the migraine‐attack threshold, allodynic migraineurs are more susceptible to triggers than the non‐allodynic ones. Objective To determine if the number of headache triggers differs between migraineurs with no/mild allodynia and those with moderate/severe allodynia. Materials and Methods We recruited 120 consecutive migraineurs. Other primary headache comorbidity and migraine prophylaxis were exclusion criteria. Each patient was interviewed according a structured questionnaire including general features about migraine, depression, and anxiety symptoms. Patients reported any migraine trigger both spontaneously and by selecting from a specific list. Allodynia during the migraine attack was measured using the Allodynia Symptoms Check‐List 12 (ASC‐12): a cut‐off of ASC‐12 score of >2 defined allodynic patients; 3‐5 score indicated mild allodynia; a 6‐8 score moderate allodynia; and score of >8 severe allodynia. Results The total number of identified triggers was significantly and positively related to allodynia measured with ASC‐12 (ρs 0.33; P < .001). In a logistic regression model, allodynia independently influenced the risk to have a higher number of triggers. Moderate/severe allodynic patients had an odds ratio of 2.8 to report a number of triggers >7 in respect to non‐/mild allodynic ones. Conclusions Migraineurs with moderate/severe allodynia had more triggers than those with no/mild allodynia. It is unknown if those with moderate/severe allodynia are more susceptible to triggers, or repetitive stimulation of the trigeminal system by triggers resulted in moderate/severe allodynia.